Komunikasi Publik SMP Negeri Tangsel dalam Implementasi Makan Bergizi Gratis - Faiz Maulana; Hekar Ramadhani; Fernanda Firrizqi (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
The Free Nutritious Meal Program (Makan Bergizi Gratis/MBG) is a strategic government initiative aimed at improving students’ nutritional quality and supporting learning concentration and academic achievement in schools. The effectiveness of this program at the school level is highly dependent on the quality of public communication carried out by schools toward internal and external stakeholders. This community service activity aims to analyze school public communication practices in supporting the implementation of the MBG program at a public junior high school in South Tangerang City. A qualitative descriptive approach was employed by collecting data through in-depth interviews with school principals, teachers, and educational staff, direct observations of school communication activities, and documentation analysis of policy guidelines and communication media. The results show that effective internal communication contributed to a shared understanding among teachers and staff regarding program objectives, implementation mechanisms, and responsibilities. Externally, communication with parents through face-to-face meetings, digital messaging groups, and online media increased parents’ understanding, participation, and trust in the program. Nevertheless, differences in parents’ information literacy and limited communication intensity remained challenges. Overall, the findings indicate that structured, transparent, and participatory school public communication positively supports the implementation of the MBG program, as reflected in reduced misinformation, improved parental acceptance, and smoother program execution.